The impact of locoregional treatment on survival of patients with primary metastatic breast cancer - Liubota, R.; Cheshuk, V.; Vereshchako, R.; Zotov, O.; Zaichuk, V.; Anikusko, N.; Liubota, I. (Experimental Oncology, 2017)
The aim of the study was to investigate the impact of primary tumor locoregional treatment (surgery or/and radiotherapy) on overall survival in patients with primary metastatic breast cancer (PMBC). Materials and Methods: This retrospective study included 295 wo men aged from 23 to 76 years with PMBC. Among the 295 patients, the effect of locoregional treatment of primary tumor on survival outcomes was evaluated in 177 women with distant metastases at diagnosis of breast cancer. 35 patient received breast surgery (group 1), 95 patients with PMBC — radiotherapy (group 2) and 47 patients — combination of breast surgery and radiation (group 3). The remaining 118 patients didn’t receive surgery or/and radiotherapy (group 4). All patients received systemic cytotoxic chemotherapy. Results: The groups of patients with PMBC did not differ significantly by age, menstrual function, ER status, Her2 receptor status, site of metastasis and number of metastatic lesions. 2- and 5-year overall survival in patients of group 1 was 54 and 32%, group 2 — 47 and 8%, group 3 — 73 and 18%, whereas in patients from group 4 — 26 and 9%, respectively. The median survival of patients who underwent surgery was 36 months, patients with PMBC who received radiotherapy — 24 months, patients who obtained combination of breast surgery and radiation — 30 months vs 18 months in patients who did not undergo primary tumor locoregional treatment. Conclusions: The results of this study showed a favourable effect of locoregional treatment in patients with PMBC.